New Markets and Their Supporting Institutions: Opportunities and Constraints for Demand Growth - Henson, Spencer (Washington, DC: World Bank, 2012)
The opportunities and challenges faced by developing countries in the context of high-value markets for agricultural and food products, both in industrialized countries and domestically, are outlined. The critical question is how to facilitate the greater participation of developing countries and lower-income countries where agriculture plays a greater economic role in such markets, while enhancing the competitive position of those countries that have already established a market position. It is critical that developing countries adopt a strategic approach to identifying and exploiting high-value market opportunities for agricultural and food products. Low-income countries, which actually have the most to gain in terms of agricultural development, rural poverty alleviation and overall economic growth, will face the biggest challenges and also have the greatest resource constraints.